Pengaruh Current Ratio, Return on Assets dan Fixed Asset Rtio terhadap Debt to Equity Ratio dengan Ukuran Perusahaan sebagai Variabel Moderating (Studi Empiris pada Perusahaan Property dan Real Estate Tahun 2017-2021) - Winda Tri Utari; Muhammad Arief (Universitas Muhammadiyah Enrekang, 2023)
The purpose of this study was to examine and analyze the effect of current ratio, return on assets and fixed asset ratio on debt to equity ratio with firm size as moderating variable. The approach used in this research is a quantitative approach. The population in this study are all property and real estate companies listed on the Indonesia Stock Exchange. The sample in this study used purposive sampling totaling 40 companies. Data collection techniques in this study using documentation techniques. The data analysis technique in this study used descriptive statistical tests, classical assumption tests, model feasibility tests, hypothesis testing and moderated regression analysis.The results of this study prove that partially shows current ratio, return on assets has an effect on debt to equity ratio while fixed asset ratio has no effect on debt to equity ratio. The results of the moderating regression analysis with the residual equation show that firm size cannot moderate the effect of current ratio, return on assets and fixed asset ratioon debt to equity ratio in property and real estate companies listed on the Indonesia Stock Exchange in 2017-2021.